1988
DOI: 10.1016/0020-7292(88)90199-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some recent analgesics on labor pain and maternal and fetal blood gases and pH

Abstract: This study attempts to determine the analgesic properties of nalbuphine, pentazocine and butorphanol during labor and their potential effects on maternal and fetal blood gases and pH. Butorphanol analgesia was superior to either nalbuphine or pentazocine in relieving labor pain. The studied analgesics caused significant maternal respiratory acidosis and fetal metabolic acidosis. These acidotic changes were most marked with pentazocine, moderate with nalbuphine and minimal with butorphanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In six studies blinding was impractical as women were given different types of treatment (e.g. IM drug versus no treatment; IM drug versus TENS) (Li 1994; Neumark 1978; Rayburn 1989a; Refstad 1980; Tawfik 1982; Thakur 2004), and in a further nine studies methods were not described or were not clear (Bitsch 1980; Erskine 1985; Fieni 2000; Giannina 1995; Husslein 1987; Keskin 2003; Lisboa 1997; Mitterschiffthaler 1991; Wahab 1988).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In six studies blinding was impractical as women were given different types of treatment (e.g. IM drug versus no treatment; IM drug versus TENS) (Li 1994; Neumark 1978; Rayburn 1989a; Refstad 1980; Tawfik 1982; Thakur 2004), and in a further nine studies methods were not described or were not clear (Bitsch 1980; Erskine 1985; Fieni 2000; Giannina 1995; Husslein 1987; Keskin 2003; Lisboa 1997; Mitterschiffthaler 1991; Wahab 1988).…”
Section: Resultsmentioning
confidence: 99%
“…Women with a contraindication to pethidine or remifentanil or requesting epidural were excluded Interventions Experimental: IV PCA remifentanil, 0.5 mcg bolus per kg (based on antenatal booking weight) with 2 min lock-out, no hourly maxControl: IV PCA pethidine, 10 mg bolus, 5 min lock-out, 100 mg hourly maxAll women were given 10 mg metoclopramide IV over 8 hrs. Outcomes Maternal: pain on 10 cm VAS recorded hourly; nausea recorded on a 10 cm VAS; itching; BP pulse and respsNeonate: 1 and 5 min Apgar scores. Notes Risk of bias Bias Authors’ judgement Support for judgement Random sequence generation (selection bias) Unclear risk Not described “randomly allocated”. Allocation concealment (selection bias) Low risk “by selecting the next in a series of sealed envelopes prepared by pharmacy.” Blinding (performance bias and detection bias)Women Low risk Women were described as blind. Blinding (performance bias and detection bias)Clinical staff Unclear risk “One investigator selected the envelope and prepared the PCA pump. the pump was covered so that the other investigator, the observer, was unable to see which drug the woman was receiving.” Blinding (performance bias and detection bias)Outcome assessor Unclear risk See above. Incomplete outcome data (attrition bias)All outcomes Low risk No loss to follow-up apparent although for some outcomes it was not clear what the denominators were Selective reporting (reporting bias) Unclear risk Unclear. Other bias Low risk None apparent. Wahab 1988…”
Section: Characteristics Of Included Studies [Ordered By Study Id]mentioning
confidence: 99%
“…Mixed-action KOR agonists have been shown to be effective in relieving labor pain [44] and are more effective in women than men in a model of post-operative dental pain [19,20,21,22]. However, Fillingim et al [17] reported no sex differences using experimentally induced pain in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Opioids commonly used for labour analgesia are meperidine, morphine, fentanyl, nalbuphine and butorphanol. In a comparison with nalbuphine, pentazocine and butorphanol, acidotic changes in the foetus were most marked with pentazocin, moderate with nalbuphine and minimal with butorphanol (20). Butorphanol tartrate is a potent analgesic with partial agonist action with minimum side effects (14).…”
Section: Discussionmentioning
confidence: 99%